9 EFFECTIVENESS OF INTERVENTIONS TO SUPPORT THE TRANSITION HOME AFTER ACUTE STROKE: A SYSTEMATIC REVIEW AND META-ANALYSIS. (25th October 2022) - O'Callaghan, G; Fahy, M; Murphy, P; Langhorne, P; Galvin, R; Horgan, F
Abstract: Background: There are considerable gaps in knowledge about effective support interventions to manage the transition to home after stroke. This systematic review looked at the effectiveness of support interventions at transition from structured stroke services to independent living at home. Methods: We searched, up to June 2021, the Cochrane Central Register of Controlled Trials, and six databases including MEDLINE and Embase; and extended to trial registries, grey literature, and Google Scholar. We included randomised controlled trials recruiting stroke patients to receive either usual care or any support intervention from structured stroke services to home. The primary outcome was functional status. Two authors determined eligibility, extracted data, assessed risk of bias (ROB2) and certainty of evidence (GRADE). Where possible we performed meta-analyses using Risk Ratios (RR) or Mean Differences(MD). Results: We included 17 studies. Support interventions led to important improvements in functional status, measured by Barthel Index up to 3-months (MD 7.87 points, 95%CI:6.84 to 19.16; 620 participants; five studies; I 2 =77%). Results in the medium to long-term demonstrated small but significant functional gains (6-12 month follow-up; MD 2.91 points, 95%CI:0.03 to 5.81; 1207 participants; six studies; I 2 =84%). Certainty of evidence was low. Support interventions may improve quality of life up to 3-months (MD 1.3, 95% CI:0.84 to 1.76), and reduce depression (SMD –0.1, 95% CI:-0.29 to –0.05) and anxiety (MD –1.18, 95% CI:-1.84 to –0.52) at 6 –12 months. Effects on other secondary outcomes remain inconclusive. Conclusion: Incorporating support interventions at hospital-to-home discharge can improve functional status and other outcomes when transitioning home after a stroke. Due to study heterogeneity, the key elements of a successful transition of care interventions remain unclear. Adoption of core outcome sets in stroke research would allow for greater comparison across studies; while applying a development and evaluation framework, and engaging stakeholders, would increase understanding of stroke survivor priorities and key elements of a transition intervention.